2019
DOI: 10.1007/s12028-019-00876-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Radiographic Cerebral Small Vessel Disease with Acute Intracerebral Hemorrhage Volume, Hematoma Expansion, and Intraventricular Hemorrhage

Abstract: Background and Objective: The aim of this study was to evaluate the impact of radiographic cerebral small vessel disease (CSVD) on the severity of acute intracerebral hemorrhage (ICH) as measured by: ICH volume, hematoma expansion, and extension of intraventricular hemorrhage (IVH). Methods: CSVD was determined on baseline computed tomography (CT) scans of patients from the Ethnic and Racial Variations of Intracerebral Hemorrhage study through the extent of leukoaraiosis and cerebral atrophy using visual ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…This remodeling of microvascular wall might protect from secondary ruptures 35 . In addition, higher CMBs 7 and more severe brain atrophy, 10 both are significantly correlated with WMH, 34 have been found to be associated with smaller hematoma volume in ICH patients. Taken together, cerebral white matter might be a possible epicenter for brain protection and could heighten brain health by mechanistic pathways 36 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This remodeling of microvascular wall might protect from secondary ruptures 35 . In addition, higher CMBs 7 and more severe brain atrophy, 10 both are significantly correlated with WMH, 34 have been found to be associated with smaller hematoma volume in ICH patients. Taken together, cerebral white matter might be a possible epicenter for brain protection and could heighten brain health by mechanistic pathways 36 .…”
Section: Discussionmentioning
confidence: 94%
“…Two studies found no significant difference between WMH and hematoma volume, 7,9 which contradicted one study 8 reporting that severe WMH was independently associated with large hematoma volume in the whole population of primary ICH. More recently, Uniken Venema SM et al 10 found an opposing association of leukoaraiosis on brain CT with hematoma volume in univariable analysis, albeit not meeting statistical significance in multivariable analysis. Because of the controversies about the relationship of white matter lesions with hematoma volume, there is a need to investigate it further.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Assessment of neuroimaging and determination of hematoma volumes in the ERICH cohort has been described previously [ 20 22 ]. Initial and follow-up CT images were used to obtain the following variables: ICH location and ICH and IVH volumes, using semiautomated computerized volumetric analysis (Alice software, Parexel Corporation, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Venema et al [1] performed a study based on Ethnic and Racial Variations in Intracerebral Hemorrhage, a multicenter, racially balanced, prospective study of spontaneous intracerebral hemorrhage (ICH). The authors hypothesize that underlying cerebral small vessel disease (CSVD) and poor outcome from ICH stem from two mechanisms: (1) how CSVD affects ICH severity, and (2) CSVD's influence on brain recovery after ICH; the authors intend to address the former in this study.…”
mentioning
confidence: 99%